A law regulating the carrying of weapons in Slater, MO, Ch. 19, § 231, in Revised Ordinances of the City of Slater, Saline County, Missouri (1908). - (:unkn) unknown (General Publisher, 1908)
If any person shall, within the City limits, carry concealed upon or about his person any dangerous or deadly weapon, or shall go into any church or place where people have assembled for religious worship, or into any school room or place where people have assembled for educational, literary or social purposes, or to any election precinct on any election day, or into any court room during the sitting of court, or into any other public assemblage of persons met for any lawful purpose other than for militia drill, or meeting called under the militia law of this state, having upon or about his person any fire arms, bowie-knife, dirk, dagger, slung shot or other deadly weapon or shall, in the presence of one or more persons exhibit any such weapon in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated, or under the influence of intoxicating drinks, or shall, directly or indirectly, sell or deliver, loan or barter to any minor any such weapon, without the consent of the parent or guardian of such minor, he shall, upon conviction, be punished by a fine of not less than fifty nor more than two hundred dollars.
--
Keywords: CARRY - CONCEALED; TRANSFER - MINORS; BRANDISHING; SENSITIVE PLACES